The study of suitability of coir fibres as wrapping paper / M.A.R Yusri ...[et al.] - Yusri, M.A.R; Azmi, N.H; Mohamed, N.U; Sanusi, S.N.A; Ismail, A.M.M
investigation was developed to identify the compatibility of fibres from the coconut husk or known as coir fibre be used as the primary material in the production of paper industries, this fibres can be an alternative material it can replaced uses of wood in the future in order to protect the environment and to promote wrapping that is environmentally friendly. In addition, in this study the recycled paper was embedded in the coir fibers sample in action to hold the coir fibres together. The main purpose of this study is to determine the suitability of the coir fibres with the recycled paper and mechanical properties of paper with different volume of alkali solution and ratio of coir fibers with recycled paper. The tensile strength index and absorption test were chosen as the responses to this study and to determine the significant difference between the ratio of the coir fibres used with recycled paper and to figured out which sample is the most suitable to be used as wrapping paper. The result shows that as the alkali solution increased, the mechanical properties of paper increased. In addition, the combination of 50% of recycled paper and SO% of coir fibres has produced paper with best mechanical properties in cooking time of 90 minutes with fixed temperature of 180°C.This conclusion approved that the coir fibres can be one of the alternatives raw materials to replaced wood fibres in application for wrapping paper